Death penalty in Indonesia: between criminal law and Islamic law perspectives - Tongat, Tongat (Faculty of Law, University of Muhammadiyah Malang, 2024)
This study seeks to discuss the implication of the regulation of the death penalty following the promulgation of Law Number 1 of 2023 concerning the Penal Code which has changed the standing of the death penalty from basic punishment to special punishment seen from the perspectives of positive law and Islamic law. This study employed socio-legal methods, presenting two primary issues of the reconstruction of the regulation concerning the death penalty in Indonesia and how Islamic law reinforces the reconstruction of the regulation of the death penalty in Indonesia. This study has brought to the following two conclusions: notwithstanding its application of the death penalty in the country, Indonesia is attempting to restrict its application. The reformed Criminal Law, particularly after the promulgation of Law Number 1 of 2023 concerning Criminal Law, adjourns the death penalty, while the defendant on a death row is given a chance to fix his/her attitude for a particular period (10 years). When the defendant demonstrates a good attitude within this time frame, the imposed death penalty is superseded by imprisonment. This policy is intended to serve as the last resort when the defendant cannot be corrected and as the middle way of balancing between the pros and cons of the death penalty in Indonesia. Moreover, Islamic values as the source of law are also behind these pros and cons, reinforcing the existence of the death penalty in Indonesia, considering that the death penalty from the Islamic view remains recognized as one of the applicable punishment practices.